Recurrence rate of basal cell carcinoma among different micrographic surgery techniques: systematic review with meta-analysis - Lacerda, P. N. [UNESP]; Lange, E. P.; Luna, N. M.; Miot, H. A.; Nogueira, V. S.N. [UNESP]; Abbade, L. P.F. (Wiley, 2022)
In high-risk basal cell carcinomas (BCCs), micrographic surgery (MS) has high tissue preservation and low recurrence rates. The Mohs technique is the most commonly used technique, with limited use of other MS techniques. No studies have been designed to compare the MS methods. This review aimed to assess BCC recurrence rates of different MS techniques. A systematic review and meta-analysis were conducted to search for related studies in PubMed, LILACS, EMBASE, SCOPUS, WEB OF SCIENCE, CINHAL and COCHRANE until March 2021. Randomized clinical trials (RCTs) and observational studies involving patients with BCC and indications for different MS techniques were included. Study selection and data extraction were performed independently by three peer reviewers, as was the risk of bias assessment using the Joanna Briggs Institute tool. Pooled estimates were assessed using the random-effects model (Logit), and heterogeneity was assessed by the chi-squared test (χ2). Stata Software version 17.0 was used for analysis. Eighteen studies were included, two RCTs and sixteen observational studies. The overall recurrence rate was 2% (95% CI, 1.0–3.0%; χ2 = 46.2; P = 0.00; 18 studies, 10 424 BCCs). In studies using the Mohs technique, the recurrence rate was 3.0% (95% CI, 1.0–5.0%; χ2 = 11.0; P = 0.00; 6 studies; 1,582 BCCs), with the Munich technique 3.0% (95% CI, 2.0–5.0%; χ2 = 0.0; no heterogeneity; 3 studies; 404 BCCs), with Tubingen technique 1% (95% CI, 1.0–2.0%; χ2 = 12.1; P = 0.00; 8 studies; 8374 BCCs) and with the Muffin technique 0.0% (95% CI, 0.0–6.0%; 1 study; 64 BCCs). Relapse rates between MS techniques were low and appeared to be similar. However, the design of this review and the absence of primary studies that directly compare the techniques do not allow us to assert the superiority between them.